Kegiatan Peningkatan Pengetahuan Masyarakat Melalui Pendidikan dan Pelatihan Kewirausahaan Di Desa Gejlik Pekalongan - Aisatul Munadaroh; Mohammad Syaifuddin; Wahid Wachyu Adi Winarto (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2022)
The part that needs to be improved from the Gejlik Village community is increasing the community's ability to master knowledge in terms of entrepreneurship and how to market their products. The service team teaches regularly in Gejlik Village once a week, to be precise on Sundays, to improve the ability of the people in Gejlik Village. Continuous training is needed to have a profound effect on increasing these abilities. Teaching is carried out by a service team that has an educational background both from a scientific background and several successful entrepreneurial practitioners. The training has resulted in a significant improvement because this program has actually been going on for 2 months. The community's motivation to learn also becomes greater as evidenced by their great enthusiasm in practicing what is exemplified by the teacher. Based on these findings, it can be concluded that the implementation of this PKM has been effective. In addition, the knowledge of the village community towards the material that has been delivered has increased.